Development of exchange trade institutions in Ukraine - Малишко, Володимир Миколайович; Присяжнюк, Ірина Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Effective activity of the modern market directly depends on environment in which it is. One of major factors that provide development of the market relations is development of institutes of exchange trade. The article is devoted to the history of the national exchange market creation. The exchange has been one of the world pillars on which the civilized market economy is based. In the West countries the exchange has a leading place among other economic institutions and has proved its public importance. In Ukraine, as well as in some other post-socialist countries, place of the exchange hasn’t been determined yet. Features of emergence of the exchanges in Ukraine related to the necessity of organizing economic life of the region. With the development of the exchanges activity Ukraine was incorporated into the system of international exchange trading, in particular the trade in grain, sugar, cattle and many other types of products.